2003
DOI: 10.1042/bj20021274
|View full text |Cite
|
Sign up to set email alerts
|

Differential signalling by muscarinic receptors in smooth muscle: m2-mediated inactivation of myosin light chain kinase via Gi3, Cdc42/Rac1 and p21-activated kinase 1 pathway, and m3-mediated MLC20 (20 kDa regulatory light chain of myosin II) phosphorylation via Rho-associated kinase/myosin phosphatase targeting subunit 1 and protein kinase C/CPI-17 pathway

Abstract: Signalling via m3 and m2 receptors in smooth muscles involved activation of two G-protein-dependent pathways by each receptor. m2 receptors were coupled via Gβγ i3 with activation of phospholipase C-β3, phosphoinositide 3-kinase and Cdc42/Rac1 (where Cdc stands for cell division cycle) and p21-activated kinase 1 (PAK1), resulting in phosphorylation and inactivation of myosin light chain kinase (MLCK). Each step was inhibited by methoctramine and pertussis toxin. PAK1 activity was abolished in cells expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
250
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(274 citation statements)
references
References 48 publications
20
250
4
Order By: Relevance
“…The pathway in circular smooth muscle, as previously shown, involves sequential activation of G q and/or G 13 , p115 RhoGEF, and RhoA (20,37,38,41,42). RhoA initiates two pathways involving activation of Rho kinase and PKC, both of which participate in inhibition of MLCP: Rho kinase via phosphorylation of MYPT1 at Thr 696 , and PKC, via phosphorylation of CPI-17, an endogenous inhibitor of MLCP, at Thr 38 (41,42). In addition, Rho kinase activates ZIP kinase (4,11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pathway in circular smooth muscle, as previously shown, involves sequential activation of G q and/or G 13 , p115 RhoGEF, and RhoA (20,37,38,41,42). RhoA initiates two pathways involving activation of Rho kinase and PKC, both of which participate in inhibition of MLCP: Rho kinase via phosphorylation of MYPT1 at Thr 696 , and PKC, via phosphorylation of CPI-17, an endogenous inhibitor of MLCP, at Thr 38 (41,42). In addition, Rho kinase activates ZIP kinase (4,11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in intestinal circular smooth muscle have shown that muscarinic m2 receptors are coupled to pertussis toxin (PTx)-sensitive G i3 , whereas m3 receptors are coupled to G q and G 13 (4,41). The specific proteins coupled to m2 and m3 receptors in longitudinal smooth muscle have not been identified.…”
Section: Distinctive Pattern Of Activation Of G Proteins By Muscarinimentioning
confidence: 99%
See 3 more Smart Citations